2020
DOI: 10.1016/j.foodhyd.2020.106013
|View full text |Cite
|
Sign up to set email alerts
|

Development of electrospun active films of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by the incorporation of cyclodextrin inclusion complexes containing oregano essential oil

Abstract: Oregano essential oil (OEO) has good antioxidant and antimicrobial activity and its incorporation into food packaging is challenging because of its intense flavor, high volatility and instability, and insolubility in aqueous systems. Additionally, the sensory perception of EO can be changed as a consequence of oxidation, heating, volatilization or chemical interactions. Cyclodextrins (CDs) can be used to avoid these inconveniences because they are able, due to their peculiar chemical structure, to encapsulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Similar results were obtained by da Silva et al ( 72 ), who observed that eugenol entrapped in cellulose nanostructures and then incorporated in the poly(butylene adipate- co -terephthalate) (PBAT) prepared by solvent casting improved the thermal stability of pure eugenol. Likewise, the previous reports of our research group agreed with the thermal properties attain in the present study, showing that the thermal stability of essential oils incorporated into PHAs by electrospinning was improved ( 59 , 67 , 73 ). Therefore, the development of thermally stable systems expands the potential use of electrospinning for the design of active food packaging as an alternative to melt processing technologies such as extrusion or compression molding.…”
Section: Resultssupporting
confidence: 93%
“…Similar results were obtained by da Silva et al ( 72 ), who observed that eugenol entrapped in cellulose nanostructures and then incorporated in the poly(butylene adipate- co -terephthalate) (PBAT) prepared by solvent casting improved the thermal stability of pure eugenol. Likewise, the previous reports of our research group agreed with the thermal properties attain in the present study, showing that the thermal stability of essential oils incorporated into PHAs by electrospinning was improved ( 59 , 67 , 73 ). Therefore, the development of thermally stable systems expands the potential use of electrospinning for the design of active food packaging as an alternative to melt processing technologies such as extrusion or compression molding.…”
Section: Resultssupporting
confidence: 93%
“…A polymer-free electrospinning approach was applied on CD inclusion complexes to enhance the water solubility; improve the high temperature stability and control the release of carvacrol [ 90 ], tymol [ 91 ], camphor [ 92 ], menthol [ 93 ], limonene [ 94 ], citral [ 95 ], cineole and p-cymene [ 96 ] and eugenol [ 97 ]. In other studies, the volatiles/inclusion complexes with CDs were incorporated in a biopolymer matrix as zein [ 98 , 99 ], o pullulan [ 100 ], semisynthetic polymers such as cellulose acetate [ 101 ] or synthetic polymers such as poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) [ 102 ] via electrospinning. These polymers have been used for the formation of edible or biodegradable antimicrobial films, as well as porous membranes for packaging or biomedical applications.…”
Section: Methods Of Preparation For Micro/nanoencapsulation Of Flamentioning
confidence: 99%
“…In order to meet the material safety requirements of food packaging, safe and non-toxic natural polymers are usually selected, such as oregano essential oil for its significant antibacterial effect [ 162 ]. Lopez produced packaging films of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) with alpha- and gamma-cyclodextrins (α-CD and γ-CDs) containing oregano essential oil (OEO).…”
Section: Application Of Transparent Electrospun Fibrous Membranementioning
confidence: 99%